Temporary Work Visas as US-Haiti Development Cooperation: A Preliminary Impact Evaluation - Michael A. Clemens; Hannah M. Postel (Institute of Labor Economics (IZA), 2017)
We report a small-sample, preliminary evaluation of the economic impact of temporary overseas work by Haitian agricultural workers. This work occurs in the United States in the context of a pilot program designed as a form of post-disaster development assistance to Haiti. We find that the effects of matching new seasonal agricultural jobs in the US with Haitian workers differs markedly from the effects of more traditional forms of assistance to Haiti, in three ways: The economic benefits are shared roughly equally between Haiti and the United States; these benefits are very large, including raising the value of Haitian workers' labor by a multiple of fifteen; and the portion of the benefits accruing to Haiti is uncommonly well targeted for the direct benefit of poor Haitian households. We discuss implementation challenges faced by the program and the potential for policies of this kind to complement more traditional forms of development and humanitarian assistance.
Keywords: F22; O15; O22; R23; 330; development; policy; aid; assistance; migration; mobility; poverty; guest work; agriculture; farm